Decreased xCT activity in patients associated with Helicobacter pylori infection - Wang, Ling; Li, Wen-Qun; Liu, Fen; Li, Yuan-Jian; Du, Jie (Frontiers in Pharmacology, 2022)
Objective: In animals, Helicobacter pylori (Hp)-induced gastric injury is accompanied by a decrease in the activity of the cysteine/glutamate transporter (xCT), which regulates extracellular glutamate levels. However, the impact of xCT activity in patients with Hp infection remains unclear. This study aims to investigate variations of xCT activity in the gastric mucosa of patients with Hp infection and to provide a clinical basis for identifying targets related to Hp infection. Methods: Our study included a total of 67 patients with gastritis, which consisted of 44 Hp-negative and 23 Hp-positive peptic ulcer cases. The inclusion criteria used to select patients were as follows: gastric histology was determined with a gastroscope, antral biopsies were taken for urease tests, and pathology and culture were performed for analysis of Hp-colonization. The clinical characteristics of the patients were obtained, the expressions of microRNAs and xCT protein were detected using immune histochemical analysis, and the concentration of glutamate in their gastric secretion was determined. Results: The findings revealed that xCT expression was significantly lower in Hp-positive patients as compared to Hp-negative individuals, which was accompanied by a decrease in glutamate concentration in gastric juice. We also discovered a high expression of microRNAs that have been shown to negatively regulate xCT expression, in Hp-positive patients. Conclusion: Reduced xCT activity in patients may play an important role in gastric ulcers caused by Hp infection. Our findings suggest that the microRNA/xCT pathway could be a potential treatment target for Hp-infection-related ulcers.